Tropical wetland ecosystem service assessments in East Africa; A review of approaches and challenges. (April 2018) - Langan, Charlie; Farmer, Jenny; Rivington, Mike; Smith, Jo U.
Abstract: East African wetlands are hotspots of ecosystem services, particularly for climate regulation, water provision and food production. We review the ability of current approaches to ecosystem service assessments to capture important social-ecological dynamics to provide insight for wetland management and human wellbeing. We synthesise evidence of human influences on wetlands and gauge the suitability of models and tools for simulating spatial and temporal dynamics, and land management on multiple ecosystem functions and services. Current approaches are largely unsuitable for advancing knowledge of social-ecological system dynamics and could be greatly improved with inter-disciplinary model integration to focus upon interactions between multiple ecosystem functions and services. Modelling can alleviate challenges that tropical wetland ecosystem services management faces and support decision-making of land managers and policymakers. Better understanding of social-ecological systems dynamics is crucial in East Africa where societies are vulnerable to poverty and climate variability, whilst dependent upon agrarian-ecological based economies. Highlights: Human influences on wetland functions and services are substantial and complex. Social-ecological dynamics must inform wetland service assessments and management. Modelling requires simulating multiple interacting ecosystem functions and services. Poor wetland ecosystem services understanding undermines poverty and climate action.